The effects of catalyst conductivity and loading of dielectric surface structures on plasma dynamics in patterned dielectric barrier discharges - Neuroth, Constantin; Mujahid, Zaka-ul-islam; Berger, Birk; Oberste-Beulmann, Christian; Oppotsch, Timothy; Zhang, Quan-Zhi; Muhler, Martin; Mussenbrock, Thomas; Korolov, Ihor; Schulze, Julian (Plasma Sources Science and Technology, 2023)
Abstract Dielectric barrier discharges (DBDs) are promising tools for air pollution removal and gas conversion based on excess renewable energy. Catalyst loading of dielectric pellets placed inside the plasma can improve such processes. The effects of such metallic and dielectric catalyst loading on the discharge are investigated experimentally. A patterned DBD is operated in different He/O 2 mixtures and driven by a 10 k H z pulsed rectangular voltage waveform. Hemispherical dielectric pellets coated by different catalyst materials at different positions on their surface are embedded into the bottom grounded electrode. Based on phase resolved optical emission spectroscopy the effects of different catalyst materials and locations on the streamer dynamics are investigated. The propagation of cathode directed positive volume streamers towards the apex of the hemispheres followed by surface streamers, that move across the structured dielectric, is observed for positive applied voltage pulses. Coating the apex with a conducting catalyst results in attraction of such streamers towards the apex due to charging of this surface, while they avoid the apex in the presence of a dielectric catalyst. Surface streamers, that propagate across the hemispheres, are stalled by conducting catalysts placed on the embedded pellets as rings of different diameters, but propagate more easily across dielectric coatings due to the presence of tangential electric fields. Reversing the polarity of the driving voltage results in the propagation of negative streamers across the patterned dielectric and attenuated effects of catalytic coatings on the streamer dynamics.